Antibiotic-induced microbiome depletion alters metabolic homeostasis by affecting gut signaling and colonic metabolism - Zarrinpar, Amir; Chaix, Amandine; Xu, Zhenjiang Z.; Chang, Max W.; Marotz, Clarisse A.; Saghatelian, Alan; Knight, Rob; Panda, Satchidananda (Nature communications, 2018)
Antibiotic-induced microbiome depletion (AIMD) has been used frequently to study the role of the gut microbiome in pathological conditions. However, unlike germ-free mice, the effects of AIMD on host metabolism remain incompletely understood. Here we show the effects of AIMD to elucidate its effects on gut homeostasis, luminal signaling, and metabolism. We demonstrate that AIMD, which decreases luminal Firmicutes and Bacteroidetes species, decreases baseline serum glucose levels, reduces glucose surge in a tolerance test, and improves insulin sensitivity without altering adiposity. These changes occur in the setting of decreased luminal short-chain fatty acids (SCFAs), especially butyrate, and the secondary bile acid pool, which affects whole-body bile acid metabolism. In mice, AIMD alters cecal gene expression and gut glucagon-like peptide 1 signaling. Extensive tissue remodeling and decreased availability of SCFAs shift colonocyte metabolism toward glucose utilization. We suggest that AIMD alters glucose homeostasis by potentially shifting colonocyte energy utilization from SCFAs to glucose. Antibiotic-induced microbiome depletion is one of the most common approaches to modulate the gut microbiome. Here the authors demonstrate that it affects gut homeostasis and glucose metabolism by decreasing luminal short chain fatty acids and leading to a shift of energy utilization by colonocytes.